Geologic controls on the genesis of the Arctic permafrost and sub-permafrost methane hydrate-bearing system in the Beaufort–Mackenzie Delta - Li, Zhen; Chabab, Elena; Spangenberg, Erik; Schicks, Judith M.; Kempka, Thomas (Frontiers in Earth Science, 2023)
The Canadian Mackenzie Delta exhibits a high volume of proven sub-permafrost gas hydrates that naturally trap a significant amount of deep-sourced thermogenic methane (CH4) at the Mallik site. The present study aims to validate the proposed Arctic sub-permafrost gas hydrate formation mechanism, implying that CH4-rich fluids were vertically transported from deep overpressurized zones via geologic fault systems and formed the present-day observed GH deposit since the Late Pleistocene. Given this hypothesis, the coastal permafrost began to form since the early Pleistocene sea-level retreat, steadily increasing in thickness until 1 Million years (Ma) ago. Data from well logs and 2D seismic profiles were digitized to establish the first field-scale static geologic 3D model of the Mallik site, and to comprehensively study the genesis of the permafrost and its associated GH system. The implemented 3D model considers the spatially heterogeneously distributed hydraulic properties of the individual lithologies at the Mallik site. Simulations using a proven thermo-hydro-chemical numerical framework were employed to gain insights into the hydrogeologic role of the regional fault systems in view of the CH4-rich fluid migration and the geologic controls on the spatial extent of the sub-permafrost GH accumulations during the past 1 Ma. For >87% of the Mallik well sections, the predicted permafrost thickness deviates from the observations by less than 0.8%, which validates the general model implementation. The simulated ice-bearing permafrost and GH interval thicknesses as well as sub-permafrost temperature profiles are consistent with the respective field observations, confirming our introduced hypothesis. The spatial distribution of GHs is a result of the comprehensive interaction between various processes, including the source-gas generation rate, subsurface temperature, and the hydraulic properties of the structural geologic features. Overall, the good agreement between simulations and observations demonstrates that the present study provides a valid representation of the geologic controls driving the complex permafrost-GH system. The model’s applicability for the prediction of GH deposits in permafrost settings in terms of their thicknesses and saturations can provide relevant contributions to future GH exploration and exploitation.